COMPLIANCE, KNOWLEDGE, SOCIO ECONOMIC AND FAMILY SUPPORT IN THE TREATMENT OF PEOPLE WITH MENTAL DISORDERS (ODGJ) IN THE WORK AREA OF SERI TANJUNG COMMUNITY HEALTH CENTER OGAN ILIR REGENCY - Surahmat, Raden; Akhriansyah, Mareta; Amalia, Amalia; Agustina, Nuriza; Hidayati, Nely (Jurnal Kesehatan Saintika Meditory, 2024)
ABSTRAK Permasalahan jiwa kerap menimbulkan ketidakstabilan dalam menjalani kegiatan sehingga menjadi permasalahan serius dalam kehidupan di masyarakat terutama jika anggota keluarga yang menderita gangguan jiwa mengalami kekambuhan setelah kembali ke masyarakat. Penelitian ini bertujuan untuk mengetahui kepatuhan, pengetahuan dan dukungan keluarga pada pengobatan orang dengan gangguan jiwa (ODGJ) di wilayah kerja UPT Puskesmas Seri Tanjung Kabupaten Ogan Ilir dengan metode penelitian menggunakan metode deskriptif kuantitatif kepada 60 responden. Hasil penelitian didapatkan Kepatuhan pengobatan ODGJ masih tergolong dalam kategori sedang. Dukungan keluarga yang paling tinggi diberikan oleh keluarga adalah dalam bentuk dukungan emosional dan yang cukup dalam bentuk dukungan instrumental sedangkan dukungan yang kurang diberikan oleh keluarga dalam dukungan penghargaan dan dukungan informative. Pengetahuan pengobatan ODGJ masih tergolong dalam kategori cukup dan Kondisi Sosial ekonomi dari 60 responden yang diteliti sebanyak 51,7% responden memiliki sosial ekonomi rendah sehingga kondisi tersebut menjadi penghalang terciptanya factor pendukung terjadinya kekambuhan. Disarankan kepada pihak Puskesmas agar dapat memberikan dukungan dan fasilitas dengan mengadakan posyandu jiwa setiap bulan dan mengaktifkan kader jiwa di masing masing desa serta melibatkan keluarga dalam memberikan pemahaman, dukungan dan menimalkan biaya yang dikeluarkan keluarga sehingga dapat meningkatkan kepatuhan pengobatan Orang dengan Gangguan Jiwa (ODGJ).Kata kunci : Kekambuhan, kepatuhan, gangguan jiwa, dukungan keluarga ABSTRACT Mental problems cause instability in carrying out activities so that they become serious problems in community life, especially if there are family members who suffer from mental disorders who experience relapse after returning to society. The study aims to describe compliance, knowledge and family support for the treatment of people with mental disorders (ODGJ) in the work area of the Seri Tanjung Health Center UPT, Ogan Ilir Regency with a research method using a quantitative descriptive method to 60 respondents. The results of the study showed that compliance with ODGJ treatment was still classified as moderate. The highest family support given by the family was in the form of emotional support and sufficient in the form of instrumental support, while the support that was lacking was given by the family in the form of appreciation support and informative support. Knowledge of ODGJ treatment was still classified as sufficient and the socio-economic conditions of the 60 respondents studied were 51.7% of respondents had low socio-economic conditions so that these conditions became a barrier to the creation of supporting factors for relapse. recommendations to the Health Center to provide support and facilities by holding a monthly mental health post and activating mental health cadres in each village and involving families in providing understanding, support and minimizing costs incurred by families so as to increase compliance with treatment for People with Mental Disorders (ODGJ).Keywords: Relapse, compliance, mental disorders, family support